Lifestyle of female students and their health convictions and preferred values - Rogo, Beata (Pedagogiczny wymiar kultury fizycznej i zdrowotnej w życiu współczesnego człowieka, 2016)
Introduction: Lifestyle is one of the most important factors related to the health of each individual which can be controlled and modified. Connection between health, the quality of life and productivity at work, understandable especially for the educated and young people, is not respected by them in the preventive practice. Recently media have been alarming about the increasing statistics of obesity among young people, their poor physical and mental condition as well as the increasing number of people with so-called social diseases. The decisive factor in human proceedings includes core values that not only imply a lifestyle and its quality but also influence the development and the form of a person’s way of life. Therefore, there is a question what kind of lifestyle students of the University of Gdańsk lead and what the relation between their lifestyle, health beliefs and their core values is.Purpose: The aim of the study is to clarify the connection between the lifestyle, health convictions and preferred values of female students at the University of Gdansk.Material and methods: Dean’s groups of full-time studies were selected to take part in the study including 1st year students attending obligatory fitness classes studying at different departments during the academic year 2006/2007. The results of 150 people were analized statistically. The students were between 19–24 and the average age was 20.3. A questionnaire was used for quantitative research.Conclusions: Only 43% of students in the examined group lead healthy lifestyle which may cause concern and may suggest a lack of knowledge in this field. The quality of meals and physical activity are the variables strongly differentiating female students in terms of their lifestyles. The results confirm earlier observations, showing that female students who lead a healthy lifestyle (PLUS group) appreciate following the desire for achieving and maintaining physical fitness as it is an expression of health that they highly appreciate as a value.